2010
DOI: 10.1109/tie.2010.2041730
|View full text |Cite
|
Sign up to set email alerts
|

Rotor Position and Speed Estimation of a Variable Structure Direct-Torque-Controlled IPM Synchronous Motor Drive at Very Low Speeds Including Standstill

Abstract: Rotor position and speed estimation of a variable structure direct-torque-Rotor position and speed estimation of a variable structure direct-torquecontrolled IPM synchronous motor drive at very low speeds including standstill controlled IPM synchronous motor drive at very low speeds including standstill

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 24 publications
0
45
0
Order By: Relevance
“…This justifies the recent concentration of research efforts in the design, analysis and control of the PMSM as reported in [2][3][4][5][6][7]. Recently, several efforts have been made toward the operational comparison between the permanent magnet synchronous motor and the induction motor which, hitherto, is the workhorse of the industry.…”
Section: Introductionmentioning
confidence: 97%
“…This justifies the recent concentration of research efforts in the design, analysis and control of the PMSM as reported in [2][3][4][5][6][7]. Recently, several efforts have been made toward the operational comparison between the permanent magnet synchronous motor and the induction motor which, hitherto, is the workhorse of the industry.…”
Section: Introductionmentioning
confidence: 97%
“…Several hybrid method have been presented in the literature [20][21][22][23][24][25]. In [21,22], the changeover algorithm was performed using weighting coefficients. A linear combination between the position estimates at high and low speeds was used in [23] to get a smooth transition.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent literature, different control approaches have been applied to such space vector modulated direct torque controlled IPMSM drives in the search for more desirable drive performances in terms of both steady state and transient responses [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…They managed to achieve a significant success due to their superior performance in terms of robustness to system uncertainties, parameters variation and external disturbances. In [12] a variable structure DTC is proposed and later modified by [13]. The reference [13] employs the mathematical model of IPMSM and attempt to linearize such a system by means of choosing the appropriate stator voltage vectors and considering bounded system uncertainties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation